Polycystic Ovary Induction in Mouse by Testosterone Enanthate - Zahra Kalhori; Mehri Azadbakht; Ali Bazdar; Hadis Zeinali (Journal of Advanced Biomedical Sciences, 2013)
Background ;Objective: Polycystic ovary is the most common cause of infertility in Women. Animal models are required for understanding the pathogenesis of polycystic ovary. The objective of this study then was to develop an animal model for inducing the polycystic ovaries using testosterone enanthate.Materials & Methods: In this study, for inducing the polycystic ovary phenotype, female rats about12-14 days-old were injected daily with testosterone enanthate for 2 and 4 weeks (experiment groups: 1 and 2), while the control groups (1 and 2) were injected only with vehicle.The ovaries from both groups were fixed and then were used for histological studies.Results: Testosterone enanthate treatment causes the histological changes in mouse ovary and significantly increased the percentage of preantral and cystic follicles and decreased the percentage of antral follicles in the experiment group, comparing with the control group (P<0.05).Conclusion: It concluded that testosterone enanthate can induces polycystic ovary in mouse.